Innovative Bahavior In Higer Education Institution: Does Performance Measurement Systems Matters? - Ietje Nazaruddin; Afifah Hasna; Indah Yani (Universitas Muhammadiyah Malang, 2023)
Purpose: This study aims to empirically examine the direct and indirect effects of performance measurement systems on innovative behavior and analyze the role of psychological empowerment as an intervening variable. Methodology/approach: The study adopts a survey research design, utilizing a questionnaire distributed directly to respondents. Data were collected from 133 respondents representing eight universities in Yogyakarta. A purposive sampling technique was employed to select the sample. Data analysis was conducted using structural equation modeling. Findings: The results indicate that performance measurement systems directly impact innovative behavior. Additionally, the study reveals an indirect influence of performance measurement systems on innovative behavior through psychological empowerment. Practical implications: The study highlights the importance of developing effective performance measurement systems and creating an environment that supports psychological empowerment to enhance innovative behavior within organizations. Originality/value: The novelty of this research lies in the inclusion of psychological empowerment as an intervening variable in the relationship between performance measurement systems and innovative behavior. The findings provide practical insights for practitioners in designing effective innovation strategies and offer directions for future research in this field.